METODE BELAJAR AKTIF MODEL PENGAJARAN TERARAH DAPAT MENINGKATKAN PRESTASI PEMAHAMAN PELAJARAN PKn TENTANG NILAI PERJUANGAN YANG DIRUMUSKAN DALAM PANCASILA PADA SISWA KELAS VI SDN 026 TAMBUSAI DESA SUKAMAJU 2012/2013 - Alitonang, Muhammad (Edu Research, 2014)
There is tendency in the world of education these days to return at idea that child will learn better if environment created naturally. Learn will be more have a meaning if child "natural" by himself what is studied, not know it. Study which orienting goals domination of proven items succeed in competition ' considering' short-range, but failing in to supply child think out in long-range life. Of analyst result got that achievement learn natural student [of] improvement of cycle of I until cycle of III that is, cycle of I ( 25%), cycle of II ( 90.%), cycle of III ( 100.%).Conclusion of this research is method learn actively of directional instruction model can have an effect on positive to motivation learn Student of SD Negeri 026 Tambusai, and also model this study can be used as one of the alternative study of PKn.